2018
DOI: 10.1155/2018/3405695
|View full text |Cite
|
Sign up to set email alerts
|

Early Growth Response 1 (Egr1) Is a Transcriptional Activator of NOX4 in Oxidative Stress of Diabetic Kidney Disease

Abstract: Background NADPH oxidase 4 (NOX4) plays a major role in renal oxidative stress of diabetic kidney disease (DKD). NOX4 was significantly increased in Egr1-expressing fibroblasts, but the relationship between Egr1 and NOX4 in DKD is unclear. Methods For the evaluation of the potential relationship between Egr1 and NOX4, both were detected in HFD/STZ-induced mice and HK-2 cells treated with TGF-β1. Then, changes in NOX4 expression were detected in HK-2 cells and mice with overexpression and knockdown of Egr1. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 32 publications
1
43
0
Order By: Relevance
“…C57BL6/J male mice (Animal Center of Guangdong province, 3-4 w, 15-16 g) were used to construct the DKD model as described previously. 15 In total, 24 DKD mice were randomly assigned to four groups at 12 w. Our previous study showed that DKD mice models could be conducted successfully, and the gene expression of Egr1 was significantly higher in DKD mice than in controls at 12 w. 15 E-DM were treated with oral enalapril (5 mg/ 150 mL water). EG-DM were treated with enalapril and pGPU6-shEgr1 plasmid, GV-DM were treated with pGPU6 vector plasmid, and the remainder were controls.…”
Section: Methods and Materials Animal Modelsmentioning
confidence: 99%
See 4 more Smart Citations
“…C57BL6/J male mice (Animal Center of Guangdong province, 3-4 w, 15-16 g) were used to construct the DKD model as described previously. 15 In total, 24 DKD mice were randomly assigned to four groups at 12 w. Our previous study showed that DKD mice models could be conducted successfully, and the gene expression of Egr1 was significantly higher in DKD mice than in controls at 12 w. 15 E-DM were treated with oral enalapril (5 mg/ 150 mL water). EG-DM were treated with enalapril and pGPU6-shEgr1 plasmid, GV-DM were treated with pGPU6 vector plasmid, and the remainder were controls.…”
Section: Methods and Materials Animal Modelsmentioning
confidence: 99%
“…The pGPU6-shEgr1 plasmid (1 μg/g, Genepgarma, China, 5′-GCTGCTTCATCGTCTTCCTCT-3′) was rapidly injected into the tail vein through by hydrodynamic gene delivery every week for 4 weeks. 15,19,20 All interventions lasted for 4 weeks (12-16w). The mice were housed in separate cages in a temperature-controlled room with a 12-h light-dark cycle in a specific pathogen free environment.…”
Section: Methods and Materials Animal Modelsmentioning
confidence: 99%
See 3 more Smart Citations